Theoretical investigation on the one- and two-photon responsive behavior of fluoride ion probes based on diketopyrrolopyrrole and its π-expanded derivatives. (31st March 2016) - Zhang, Li; Zou, Lu-Yi; Guo, Jing-Fu; Ren, Ai-Min
Abstract : The intrinsic two-photon absorption properties of the studied fluoride anion probes and their corresponding reaction products are systematically investigated. Abstract : Because of the special physiological and chemical properties of the fluoride ion (F − ) and its important roles in the environment and living organisms, a series of novel F − probes based on 1, 4-diketo-3, 6-diphenylpyrrolo[3, 4- c ]pyrrole (DPP) and its π-expanded derivatives have been investigated in detail in this study. Their electronic structures and one-photon absorption (OPA) are investigated by employing the density functional theory (DFT) and time-dependent DFT (TDDFT) methods. Moreover, their two-photon absorption (TPA) properties have also been further investigated by using quadratic response theory. Our calculated results reveal that the modifications of the compounds by both increasing the number of electron-donating groups (thiophene groups) and introducing fluorene units can effectively enhance the TPA responses, making the probes, such asDPP3, DPP4 andDPP5, show relatively higher TPA cross sections ( δ TPA ) in the range of 5380.0–9500.0 GM in the near-infrared region (885.6–991.9 nm). Additionally, the strategy of modifying the compounds by using fluorene (DPP6 ), aza-BODIPY (DPP7 ) and BODIPY (DPP8 ) moieties as π-expanded central structures, respectively, is proved ideal for obtaining large δ TPA values at longer wavelengths, especially forDPP7 andDPP8, whose δ TPA values are about 2–3 times larger than that of the related DPP-Fs, which is superior to the previously reported two-photon F − probes because large δ TPA differences between probes and the reaction products are highly desirable for practical two-photon F − detection in biological systems.